Cytokines pre-determined by genetic factors are involved in pathogenesis of Rheumatoid arthritis. Issue 2 (October 2015) - Taneja, Veena
Highlights: HLA alleles positively select T cells and predetermine production of TH17/TH2 under different conditions. HLA alleles that produce TH1/TH17 cytokines and provide advantage in clearing infections have been preserved for generations. Most studies point a significant role of molecular mimicry in autoimmunity. Abstract: Rheumatoid arthritis (RA) is associated with the presence of autoreactive CD4 T cells that produce pro-inflammatory cytokines. The role of genetic factors in the predilection to develop RA is strongly supported by the increased presence of certain HLA class II molecules in patients. The HLA class II genes are highly polymorphic and are critical for generating an immune response to clear infections. Production of Th1 and Th17 response by the CD4 T cells helps to clear infections. HLA-DQ8 is a promiscuous binder and presents many peptides generating immune response and producing a Th17 response. DRB1∗0401 is associated with the production of both IL-17 and IFN-γ. Thus both DR4 and DQ8 can clear infections by producing TH1/Th17 cytokines, but their presence increases the risk of developing RA. Using transgenic mice expressing human HLA genes, we have shown that HLA polymorphism determines the cytokine profile. DRB1∗04 molecules modulate the DQ8-restricted response and determine the outcome of arthritis in mice carrying DR4/DQ8 haplotype. Thus, interaction between DQ and DR molecules determines the cytokine milieu and propensity of the HLA haplotype to predispose to autoimmunity.